Assessing the longitudinal associations and stability of smoking and depression syndrome over a 4‐year period in a community sample with type 2 diabetes 在一个社区2型糖尿病样本中进行的为期4年的吸烟与抑郁综合征之间的纵向相关性以及稳定性的评估. (2nd April 2014) - Clyde, Matthew; Smith, Kimberley J.; Gariépy, Geneviève; Schmitz, Norbert
Abstract Background The aim of the present study was to investigate the stability and longitudinal association between depression and smoking status within a community sample with type 2 diabetes (T2D) while controlling for sociodemographic and disease‐related variables. Methods Adults with T2D were recruited and agreed to be followed‐up via random digit dialing for the Montreal Diabetes Health Study. At baseline, 1614 individuals were classified as never (n = 592), former (n = 690), light (≤10 cigarettes a day; n = 128) and moderate–heavy (11+ cigarettes a day; n = 204) smokers. Depression was assessed using the Patient Health Questionnaire‐9 and individuals were classified as either "none" or having depression syndrome. Generalized estimating equations were used to test the association between depression syndrome and current smoking status while controlling for other demographic and health‐related variables. Results Prevalence rates of smoking and depression showed mild to substantial agreement over time. Depression syndrome was significantly associated with moderate–heavy smoking in the fully adjusted model using cross‐sectional (all four waves; odds ratio [OR] 1.46; 95% confidence interval [CI] 1.08–1.99; P < 0.05) and longitudinal (controlling for depression at baseline; OR 1.54; 95% CI 1.02–2.31; P < 0.05) data. Conclusions Smoking and depression prevalence rates appear to be stable over time in our community sample with T2D. Moderate–heavy smoking is strongly associated with elevated depression, both in cross‐sectional and longitudinal models. Persistent moderate–heavy smokers may be at increased risk of both physical and mental health complications. This burden is even greater for those with T2D.